Verbs with Prefix po- in Russian Dialects of Amur Region - V. T. Sadchenko (Научный диалог)
The prefix verbal lexicon is analyzed on the basis of the dialect material of the Russian dialects of the Amur region. The relevance and novelty of the work are due to both the general unresolved problem of describing the meanings of Russian verbal prefixes, and insufficient knowledge of the specifics of verbal word formation in dialects. Verbal derivatives with the prefix po- are considered. The linguistic processes accompanying the formation of these derivatives are characterized. A classification of word-formation types and patterns is proposed based on the material presented in the Dictionary of Russian Dialects of the Amur Region, their distinctive features are noted in comparison with their literary counterparts. Attention is drawn to the phenomena of polyprefixation and substitution, in which the prefix po- is involved. It is concluded that the group of Russian dialects of the Amur region is characterized by agglutination with the prepositive prefix po-. Addressing the problems of verbal prefixation in dialects of secondary formation, localized on a vast territory of late settlement, can contribute to a wider involvement of dialect material to illustrate the controversial provisions of prefixology in modern Russian, as well as to identify the features of the verbal derivation of the Russian language in the aspect of its regional existence.